1992
DOI: 10.1364/ao.31.007249
|View full text |Cite
|
Sign up to set email alerts
|

Determination of refractive properties of fluids for dual-wavelength interferometry

Abstract: Methods to calculate the refractive properties of solutions at different wavelengths are described by using experimental data at just two wavelengths. The properties are the refractive index and its gradients with temperature and concentration. Cauchy's equation is used to determine the refractive indices. The gradients versus temperature and concentration are then determined by using the Murphy-Alpert and the Lorentz-Lorenz equation, respectively. Finally, the particular case of a triglycine sulfate aqueous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…More recently, Mehta and Vikram et al have reported the applicability of this technique for determining the temperature and concentration fields inside liquids [313,562]. The principle of dual-wavelength interferometry (and holography) has been described in reports by Vikram et al [564], and is described below. The optical schematic of the two-wavelength interferometry is shown in Fig.…”
Section: Dual-wavelength Interferometrymentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, Mehta and Vikram et al have reported the applicability of this technique for determining the temperature and concentration fields inside liquids [313,562]. The principle of dual-wavelength interferometry (and holography) has been described in reports by Vikram et al [564], and is described below. The optical schematic of the two-wavelength interferometry is shown in Fig.…”
Section: Dual-wavelength Interferometrymentioning
confidence: 99%
“…Extending the above discussion to the dual-wavelength interferometry, we get two independent equations corresponding to the two source wavelengths, l 1 and l 2 , which are then solved to get the separate values for thermal and concentration variations as [564] DC ¼…”
Section: Dual-wavelength Interferometrymentioning
confidence: 99%
See 3 more Smart Citations